2001
DOI: 10.1097/00004583-200106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding AIDS-Risk Behavior Among Adolescents in Psychiatric Care: Links to Psychopathology and Peer Relationships

Abstract: Findings underscore the complexity of factors (types of informants and dimensions of psychopathology) that underlie AIDS risk in troubled youths, and they offer specific directions for designing and implementing uniquely tailored AIDS prevention programs, for example, by targeting delinquent behavior and including high-risk peers and important family members in interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
244
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(261 citation statements)
references
References 51 publications
15
244
2
Order By: Relevance
“…Parental symptom ratings on the Child Behavior Checklist (CBCL) (Achenbach, 1991a) were relatively consistent with diagnostic rates generated from the C-DISC; 50% and 49% of parents reported adolescent internalizing and externalizing symptoms in the clinical range. Rates of DISC-generated diagnoses in this sample are similar to those of other studies of general clinic populations (Jensen and Weisz, 2002).Consistent with prior research (Brown et al, 1997;DiClemente and Ponton, 1993;Donenberg et al, 2001Donenberg et al, , 2002, teens in this study reported high rates of risky sexual behavior; 39% reported ever having vaginal, anal, and/or oral sex, and among sexually active youths (n = 77), 42% had sex with a high-risk partner, 49% had sex while using drugs/alcohol, 66% had sex without Bloom, 1985) is a compendium of scales derived from other measures of family behavior. We used the five-item Family Disengagement Scale to measure the degree to which family members are involved in each others' lives (α = .50).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Parental symptom ratings on the Child Behavior Checklist (CBCL) (Achenbach, 1991a) were relatively consistent with diagnostic rates generated from the C-DISC; 50% and 49% of parents reported adolescent internalizing and externalizing symptoms in the clinical range. Rates of DISC-generated diagnoses in this sample are similar to those of other studies of general clinic populations (Jensen and Weisz, 2002).Consistent with prior research (Brown et al, 1997;DiClemente and Ponton, 1993;Donenberg et al, 2001Donenberg et al, , 2002, teens in this study reported high rates of risky sexual behavior; 39% reported ever having vaginal, anal, and/or oral sex, and among sexually active youths (n = 77), 42% had sex with a high-risk partner, 49% had sex while using drugs/alcohol, 66% had sex without Bloom, 1985) is a compendium of scales derived from other measures of family behavior. We used the five-item Family Disengagement Scale to measure the degree to which family members are involved in each others' lives (α = .50).…”
supporting
confidence: 88%
“…Externalizing problems (aggression, delinquency) are also associated with high rates of risky sex, frequent sexual activity, early sexual debut, low rates of condom use, high numbers of sexual partners, and high rates of prostitution and drug/alcohol use before and during sex (Koopman et al, 1994;Rotheram-Borus and Koopman, 1991;Rotheram-Borus et al, 1989;Stiffman and Cunningham, 1991). Among troubled teens, externalizing problems appear more strongly related to sexual risk-taking than internalizing problems (Donenberg et al, 2001), but we are not aware of any studies that have assessed the links between mental health problems and sexual debut or different mental health problems and the timing of sexual debut. Moreover, we did not find any studies of achievement motivation and self-efficacy in relation to initial sexual experience among youths in psychiatric care.…”
mentioning
confidence: 99%
“…Substance Use-Substance use was assessed with the AIDS-Risk Behavior Assessment (ARBA) (28), a computer-assisted structured interview designed specifically for use with youth to assess their self-reported sexual behavior and substance use. The ARBA was derived from five well-established measures used in large-scale studies to examine substance use, sexual behavior, and HIV/AIDS-risk behaviors in youth (28). Binge drinking was assessed with the following question, "During the last year, how often did you have 5 or more drinks of alcohol in one day (including the evening)?"…”
Section: Methodsmentioning
confidence: 99%
“…Sexual Risk Taking-A version of the AIDS-Risk Behavior Assessment (ARBA) (28) adapted for sexual minority youth was used to assess sexual risk taking. Multiple anal sex partners was coded positive for individuals who reported more than one receptive or insertive anal sex partner in the last three months, based on two free response items assessing number of sex partners for each behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation